2019
DOI: 10.1590/s1984-29612019075
|View full text |Cite
|
Sign up to set email alerts
|

Parasitological and histological aspects of Holochilus sciureus naturally infected by Schistosoma mansoni

Abstract: Schistosomiasis is a neglected disease that affects millions of people around the world, being common in the state of Maranhão. A total of 225 rodents of the Holochilus sciureus species from the Western Lowland Maranhão were studied, of which 144 animals (64%) exhibited Schistosoma eggs in their feces samples. Macroscopic lesions characterized as well-defined whitish areas on the liver and spleen surfaces were observed. Histopathological examination revealed multifocal granulomas in the esophagus, liver, splee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…Além dos moluscos transmissores, estudos também tem relatado a participação de um roedor silvestre (Holochilus sciureus) com hábito de vida semiaquático na epidemiologia da esquistossomose. A pesquisa com esse roedor no Município de São Bento (MA), mostrou que entre 225 animais, 144 (64%) exibiram ovos de Schistosoma em suas amostras de fezes podendo então desempenhar um papel como reservatório de S. mansoni nesta região, uma vez que foi encontrado naturalmente infectado (Silva-Souza et al, 2019).…”
Section: Discussionunclassified
“…Além dos moluscos transmissores, estudos também tem relatado a participação de um roedor silvestre (Holochilus sciureus) com hábito de vida semiaquático na epidemiologia da esquistossomose. A pesquisa com esse roedor no Município de São Bento (MA), mostrou que entre 225 animais, 144 (64%) exibiram ovos de Schistosoma em suas amostras de fezes podendo então desempenhar um papel como reservatório de S. mansoni nesta região, uma vez que foi encontrado naturalmente infectado (Silva-Souza et al, 2019).…”
Section: Discussionunclassified
“…Wild rodents naturally infected with S. mansoni follow the same pattern of eosinophil infiltration with the formation of typical granulomas, as seen in Figure 1 A. Histopathological studies of target organs in naturally Schistosoma -infected H. sciurus and N. squamipes describe the initial stages of hepatic granulomas with marked inflammatory infiltrates rich in eosinophils [ 118 , 119 , 120 ]. An intense and diffuse infiltration of eosinophils surrounding eggs in the lamina propria of the H. sciurus esophagus has also been reported [ 121 ]. Costa Silva and colleagues [ 122 ] showed that the initial hepatic exudative Schistosoma granulomas in naturally infected N. squamipes are rich in diffusely distributed eosinophils, with a focal concentration around the eggs.…”
Section: Eosinophils In Natural Models Of Schistosomiasismentioning
confidence: 99%
“…Em um dos artigos analisados com descritor "Schistosoma mansoni" and "Maranhão", que se trata de uma pesquisa realizada recentemente na Planície Ocidental do Maranhão, há evidência de uma grande quantidade de roedores infectados da espécie Holochilus sciureus, a pesquisa mostra que de 225 roedores que foram estudados, 144 animais (64%) apresentaram ovos de S. mansoni em suas fezes, no entanto, essa pode ser mais uma preocupação com a transmissão da doença, já que as fezes infectadas fazem parte do ciclo do verme (SILVA-SOUZA et al, 2019).…”
Section: Prospecção Cientíicaunclassified